Adultery in Perspective of Indonesian Criminal Law and Islamic Criminal Law - Miswardi Miswardi (Budapest International Research and Critics University, 2022)
As a country that adheres to the Pancasila ideology, and places the precepts of divinity as the first precept of Pancasila, Indonesia should be a religious country that is thick with religious nuances, and free from heinous acts and evil deeds. But in fact, Indonesia is currently experiencing moral degradation and no longer reflects religious values. This is marked by a statement of actions that violate religious norms and state rules. One example is the problem of adultery that knows no age and social status. In fact, regarding this issue there are indications of omission and protection, because so far there has been no legal certainty in its resolution. Furthermore, in legal disputes the issue of adultery is actually included in the complaint offense. Of course, this problem has bad implications for its identity as a religious nation. Therefore, it is not wrong if the role of Indonesia's national criminal law is questioned by many parties. On the one hand, we believe that criminal law is the ultimum remedium as a controller or regulation of criminal acts. In social reality, throughout the history of human civilization, adultery has never stopped, even now it is growing and the perpetrators come from various circles and layers of society, which are not limited by age and profession. Therefore, this paper will analyze how the law actually anticipates this phenomenon, both in the perspective of Indonesian national criminal law and Islamic criminal law.